Management and Organization Review Special Issue 'Social Networks ‒ The Dark and Bright Sides of Informal Networks'. (22nd June 2018) - Horak, Sven; Afiouni, Fida; Bian, Yanjie; Ledeneva, Alena; Muratbekova-Touron, Maral; Fey, Carl
Abstract : Research on the mechanisms of organizing and managing via interpersonal relations has a rich history in the management and organization-oriented literature. So far, however, the informal dimension of managing and organizing by drawing on informal networks in an international context has received comparably less attention. Recent research has pointed out that social capital and network theories have largely been developed by Western scholars based on circumstances and social structures that are typical of Western societies. Thus, current theory takes into account to a lesser extent their character and nature and the way in which informal ties and networks are formed in other parts of the world (Ledeneva, 2018 ; Li, 2007b ; Qi, 2013 ; Sato, 2010 ). Besides the growing body of literature concerned with informal ties and networks in emerging and transitioning countries, for example guanxi (China), blat/ svyazi (Russia), and wasta (Arab World), a trend for analyzing pervasive informal networks in advanced and industrialized economies, such as yongo (Korea), has arisen. While insights from the latter research stream indicate that informal networks persist, the results generated in both research streams will help in developing the extant informal network theories further.